Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3389/fphys.2019.00752
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acute Continuous Hypoxia on Triglyceride Levels in Constantly Fed Healthy Men

Abstract: Introduction Elevated plasma triglyceride (TG) concentrations are an important contributor to deleterious metabolic alterations. Evidence in animals suggest that acute exposure to an environment with reduced oxygen inhibits plasma TG clearance and causes important rise in plasma TG, especially in the postprandial state. The objective of this study was to characterize the effects of an acute exposure to normobaric hypoxia on prandial TG levels in 2 distinct lipoprotein subtypes in healthy humans: c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 30 publications
1
11
1
Order By: Relevance
“…Assuming that lipid absorption is not affected by hypoxia, the present study suggests that hypoxia may also impair the clearance of TRL-TG as shown by the accumulation of buoyant TRL TG under IH in the control group. Taken together, recent [ 27 ] and current results suggest that alteration in plasma TG under hypoxia in healthy individuals seems to occur only in the prandial and postprandial states and that the intensity of the lipid challenge, measured in terms of peak triglyceridemia, may be a critical factor for these effects to be observed. Our initial hypothesis that individuals with OSA would display an altered postprandial triglyceridemia was confirmed based on the fact that plasma TG were still on average significantly higher in the OSA group 6-h post meal ingestion under normoxia.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Assuming that lipid absorption is not affected by hypoxia, the present study suggests that hypoxia may also impair the clearance of TRL-TG as shown by the accumulation of buoyant TRL TG under IH in the control group. Taken together, recent [ 27 ] and current results suggest that alteration in plasma TG under hypoxia in healthy individuals seems to occur only in the prandial and postprandial states and that the intensity of the lipid challenge, measured in terms of peak triglyceridemia, may be a critical factor for these effects to be observed. Our initial hypothesis that individuals with OSA would display an altered postprandial triglyceridemia was confirmed based on the fact that plasma TG were still on average significantly higher in the OSA group 6-h post meal ingestion under normoxia.…”
Section: Discussionsupporting
confidence: 76%
“…This divergence could possibly be attributed to the fact that, for unclear reasons, higher average peak postprandial TG concentrations were achieved in the present study (~ 3 mmol/L) compared to the previous one (~ 2 mmol/L). The higher postprandial triglyceridemia achieved in the present study could also be responsible for the fact that we observed a trend toward an increase in the TG content of buoyant TRL, an effect that was not seen in a previous study we conducted in healthy young men in prandial state under continuous hypoxia (in which plasma TG concentrations around 1.8 mmol/L were achieved on average) [ 27 ]. This last study allowed us to hypothesize that hypoxia, in healthy individuals, may increase the hepatic production of VLDL-TG in response to an increase in lipid influx in the form of elevated plasma NEFA and chylomicron remnants.…”
Section: Discussioncontrasting
confidence: 46%
See 3 more Smart Citations